Optimization of ground plane antenna gain by increasing the inductance of loading coil based on silver material - Suyanta Suyanta; Arief Marwanto; Suryani Alifah (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
To overcome the attenuation due to signal distortion in the telex model antenna transmitter, the copper and silver coil loading materials for gain have been tested. The parameters include standing wave ratio (SWR) value≈1, the antenna impedance (ZL), return loss (RL), reflection coefficient (ρ) which measured the bandwidth (BW) and quality factor (Q). In this experiment a telex model ground antenna is used, a coaxial feeder cable with 50 Ω and an operating frequency of 144.280 MHz was used. The feeder cable is tuned to approximate pure resistive with minimum impedance to reach maximum resonance frequency. The field strength effective radiated power (ERP) is measure based on 4 measurement points which has different distances within 100 km areas. The results show that the antenna based on copper loading coil (CLC) has a bandwidth is BW=5.166 MHz and Q=27.929, moreover, the silver loading coil (SLC) antenna the bandwidth is BW=4.500 MHz and Q=32.062. Therefore, SLC material could provide a good reduction in attenuation of signal distortion when signal radiation occurs from the antenna to the air.